Adverse Outcomes with Maternal Blood Pressure Less than 140/90 in Pregnancy Complicated by Hypertension - Mitchell, Courtney J.; Tita, Alan; Anderson, Sarah B.; Pasko, Daniel N.; Harper, Lorie M. (American Journal of Perinatology, 2019)
Objective We assessed the risk of small for gestational age and other outcomes in pregnancies complicated by chronic hypertension with blood pressure <140/90 mm Hg.Study Design Retrospective cohort of singletons with hypertension at a single institution from 2000 to 2014. Mean systolic blood pressure and mean diastolic blood pressure were analyzed as continuous and dichotomous variables (<120/80 and 120–139/80–89 mm Hg). The primary outcome was small for gestational age. Secondary outcomes included birth weight, preeclampsia, preterm birth <35 weeks, and a composite of adverse neonatal outcomes.Results Small for gestational age was not increased with a mean systolic blood pressure <120 mm Hg compared with a mean systolic blood pressure 120 to 129 mm Hg (adjusted odds ratio [AOR] 1.6; 95% confidence interval [CI] 0.92–2.79). Mean diastolic blood pressure <80 mm Hg was associated with a decrease in the risk preeclampsia (AOR 0.57; 95% CI 0.35–0.94), preterm birth <35 weeks (AOR 0.35; 95% CI 0.20–0.62), and the composite neonatal outcome (AOR 0.42; 95% CI 0.22–0.81).Conclusion Mean systolic blood pressure <120 mm Hg and mean diastolic blood pressure <80 mm Hg were not associated with increased risk of small for gestational age when compared with higher, normal mean systolic and diastolic blood pressures.
Keywords: fetal; growth restriction; hypertension; preeclampsia